2024
DOI: 10.1021/acsami.4c00619
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Nature of Distant Interaction of the Atmospheric Pressure Helium Plasma Discharge Tube with Glioblastoma Cancer Cells

Denis B. Zolotukhin,
Alex Horkowitz,
Michael Keidar

Abstract: Atmospheric pressure coaxial gaseous discharge tubes (DTs) with helium have demonstrated potential for in vitro inactivation or sensitization of glioblastoma cancer cells. Here, we study the effect of two configurations of the DT electrode system on its electromagnetic emissivity as well as other physical factors (heating and UV emission) that form in the vicinity of this device. We demonstrate that the configuration of the DT electrodes that concentrates the discharge streamers near the top of the device has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Recent studies have demonstrated that CAP generated in a confined, dielectric vessel, further referred to as a discharge tube (DT), can also reduce cell viability and sensitize U87-MG cells to the primary glioblastoma chemotherapeutic temozolomide (TMZ) [10]. The spatial distribution of DT generated electric fields and thermal effects have recently been determined, demonstrating the ability to non-invasively treat cells at a distance of 1-2 cm [11]. The addition of a cooling fan system to the DT also eliminates the thermal effects, allowing for bioeffects study without the impact of thermal effects [11].…”
Section: Cold Atmospheric Plasmamentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have demonstrated that CAP generated in a confined, dielectric vessel, further referred to as a discharge tube (DT), can also reduce cell viability and sensitize U87-MG cells to the primary glioblastoma chemotherapeutic temozolomide (TMZ) [10]. The spatial distribution of DT generated electric fields and thermal effects have recently been determined, demonstrating the ability to non-invasively treat cells at a distance of 1-2 cm [11]. The addition of a cooling fan system to the DT also eliminates the thermal effects, allowing for bioeffects study without the impact of thermal effects [11].…”
Section: Cold Atmospheric Plasmamentioning
confidence: 99%
“…The spatial distribution of DT generated electric fields and thermal effects have recently been determined, demonstrating the ability to non-invasively treat cells at a distance of 1-2 cm [11]. The addition of a cooling fan system to the DT also eliminates the thermal effects, allowing for bioeffects study without the impact of thermal effects [11]. With this in mind, the present study investigates the bioeffects of DT treatment on U87-MG glioblastoma multiform cancer cells considering separation distance between DT and cell samples, treatment duration, multiple treatments, incubation time post treatment, and screening of EM frequency bands by solid and liquid barriers.…”
Section: Cold Atmospheric Plasmamentioning
confidence: 99%
See 3 more Smart Citations